2003
DOI: 10.1023/a:1024633230584
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The effectiveness of EMG biofeedback training for tension headache has been well established. Previous studies evaluating changes in an average EMG activity score from pre- to posttreatment have not consistently found a relationship between a reduction in average EMG activity and headache improvement at posttreatment. The current study is a preliminary analysis of the utility of EMG variance as another possible mechanism of change. Frontalis EMG average activity and variances from 6 chronic tension-type headac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…For EMG, it has previously reported that the variance of EMG may provide additional information that is “lost” when using only an average EMG amplitude as EMG variance may indicate how the average muscle activity is occurring [43]. And fortunately, EMG and SMG themselves demonstrated good correlation, as shown in Figure 8, though they represented two distinct genres of signals generated during the muscle contractions.…”
Section: Discussionmentioning
confidence: 95%
“…For EMG, it has previously reported that the variance of EMG may provide additional information that is “lost” when using only an average EMG amplitude as EMG variance may indicate how the average muscle activity is occurring [43]. And fortunately, EMG and SMG themselves demonstrated good correlation, as shown in Figure 8, though they represented two distinct genres of signals generated during the muscle contractions.…”
Section: Discussionmentioning
confidence: 95%
“…However, there were only a few studies evaluating the impairment of masticatory system based on an EMG signal analysis. Cruccu et al (10) and Wang et al (11) used a linear EMG parameter, root mean squares (RMS), to evaluate the excitability of muscles (12) and found that the activation of the masticatory muscles was lower in the affected side of patients poststroke during clenching. Another linear parameter, median frequency (MDF), is also widely used to describe spectral characteristics of EMG signals with a good specificity and sensitivity in reflecting the muscle electrophysiology (13, 14).…”
Section: Introductionmentioning
confidence: 99%